Questioning the use of tourniquets in carpal tunnel surgery and determining ideal level - Cengiz Aldemir; Fatih Duygun (Medicine Science, 2017)
Our aim was to determine if tourniquet use was a requirement in CTS release surgery, by evaluating patients in which tourniquets were used at different levels and patients in which tourniquets were not used during surgery. A total of 48 patients were included in the study. Eighteen patients had bilateral carpal tunnel syndrome. In these patients, the surgery of one side was performed with a forearm tourniquet, while the other side was performed with the conventional upper arm tourniquet. Thirty patients underwent carpal tunnel release surgery without a tourniquet. The duration of surgery, heart rate, blood pressure, pain status (visual analogue scale) of all patients, and the blood loss of patients who underwent surgery without a tourniquet were recorded. When the tourniquet and no-tourniquet groups were compared, there were no significant differences in terms of pain and physiological response. However, patient satisfaction was higher in the no-tourniquet group while operation times were longer. We believe that the local anesthetic + epinephrine without tourniquet method is advantageous compared to the other methods. [Med-Science 2017; 6(4.000): 753-755]